The Ecological Construction and Sustainable Development of University-Enterprise Cooperation in English Education in the Era of Artificial Intelligence - Yang, Ying (Pinnacle Academic Press Proceedings Series, 2026)
In the era of artificial intelligence (AI), English education is undergoing a profound transformation from traditional knowledge transmission to intelligent, interactive, and practice-oriented models. University–enterprise cooperation has become a key mechanism for aligning academic training with evolving industry demands, cultivating application-oriented talents, and promoting educational innovation. This study investigates the ecological construction and sustainable development of university–enterprise cooperation in AI-driven English education from a systems perspective. It first clarifies the theoretical correlations among AI, educational ecology, and sustainable development, emphasizing the dynamic balance between technological progress, institutional arrangements, and humanistic values. The paper then explores four core mechanisms of AI-driven cooperation: innovation in teaching models through intelligent platforms and data-driven feedback; integration of talent training with employment pathways; coordination of industrial structure with curriculum design; and co-creation of organizational culture and value systems between universities and enterprises. Based on an analysis of current practices, the study identifies major challenges, including uneven cooperation quality, insufficient depth of innovation, weak integration of resources, and an imbalance between technological empowerment and humanistic education. In response, four optimization paths are proposed: strengthening policy and institutional guarantees, deepening the integration of industry, education, and technology, enhancing talent cultivation and brand building, and promoting sustainable development with explicit humanistic protection. The findings provide a reference for constructing a resilient, open, and future-oriented cooperative ecosystem that supports educational modernization and industrial upgrading.